Immunotherapy associated central nervous system complications in primary brain tumors - Mantica, Megan; Drappatz, Jan (Frontiers in Oncology, 2023)
Advances clarifying the genetics and function of the immune system within the central nervous system (CNS) and brain tumor microenvironment have led to increasing momentum and number of clinical trials using immunotherapy for primary brain tumors. While neurological complications of immunotherapy in extra-cranial malignancies is well described, the CNS toxicities of immunotherapy in patients with primary brain tumors with their own unique physiology and challenges are burgeoning. This review highlights the emerging and unique CNS complications associated with immunotherapy including checkpoint inhibitors, oncolytic viruses, adoptive cell transfer/chimeric antigen receptor (CAR) T cell and vaccines for primary brain tumors, as well as reviews modalities that have been currently employed or are undergoing investigation for treatment of such toxicities.